STUDENTS’ PERCEPTION OF USING ENGLISH SONGS AND THEIR VOCABULARY LEARNING - Windy Fransisca (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aims to know students’ perception of using English songs and their vocabulary learning. The design of this research was a qualitative with a case study design. There were 25 students of eight semester of English education Department of University of Islam Malang as the subjects of this study. The data were collected by questionnaire and interview. To analyzed the data from questionnaires, the researcher used formula of percentage calculations based on Sugiyono (2015). Meanwhile, the data from the interview were analyzed by using the flow model by Miles and Huberman as cited in Sugiyono (2015) which consisted of data display, data reduction, and drawing a conclusion. The result of this study showed students’ perception of using English songs and their vocabulary learning were positive. The majority of the students had an interest in listening English songs. They always updating the latest English songs and spend their time to listening English songs. Almost all of the students also agreed that English songs can help them in a learn English skills and increasing their vocabulary. In addition, all participants said that pop songs gave the best results to increase vocabulary because pop songs have a slow tempo, making it easier for students to understand the meaning of the lyrics of the song. Based on the findings, it is suggested for further research to investigate students’ perceptions of using English songs and others English skills.Keywords: Students’ perception, English songs, vocabulary learning